2004
DOI: 10.1038/sj.ijir.3901285
|View full text |Cite
|
Sign up to set email alerts
|

Retention and migration of alprostadil cream applied topically to the glans meatus for erectile dysfunction

Abstract: Retention and migration of a specially designed alprostadil transdermal cream was assessed after single-dose administration to the glans meatus of the penis. Seven men were enrolled in this twoway crossover study. Three subjects self-administered the radio-labeled alprostadil transdermal cream (B100 mg of cream containing 300 lg alprostadil) by inserting the tip of the dispenser into the meatus. In three others, the dose was administered by dispensing the cream dropwise into the metal opening without touching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Use of excipients to enhance transdermal drug delivery from topical formulations is a useful strategy employed to optimize delivery as an alternative to injection or insertion [19]. Topical alprostadil cream is a formulation of alprostadil in a novel, proprietary, skin‐permeation‐enhancing drug delivery platform that has been shown to improve erectile function in male patients with mild, moderate, and severe ED [20–22]. The cream is provided in a novel unit‐dose dispenser and is applied onto the meatus and glans of the penis resulting in a short‐term change to the permeation dynamics of the tissue allowing for rapid transdermal penetration of alprostadil with efficacy observed within 5–30 minutes after application [20].…”
Section: Introductionmentioning
confidence: 99%
“…Use of excipients to enhance transdermal drug delivery from topical formulations is a useful strategy employed to optimize delivery as an alternative to injection or insertion [19]. Topical alprostadil cream is a formulation of alprostadil in a novel, proprietary, skin‐permeation‐enhancing drug delivery platform that has been shown to improve erectile function in male patients with mild, moderate, and severe ED [20–22]. The cream is provided in a novel unit‐dose dispenser and is applied onto the meatus and glans of the penis resulting in a short‐term change to the permeation dynamics of the tissue allowing for rapid transdermal penetration of alprostadil with efficacy observed within 5–30 minutes after application [20].…”
Section: Introductionmentioning
confidence: 99%
“…The alprostadil cream is minimally absorbed in the systemic circulation (98% is retained in the navicular fossa; Cuzin, ; Moncada, ); therefore, there is a low risk of systemic adverse events (3%), and there are no interactions with food, drugs, and alcohol. Local adverse effects (65%) are mild to moderate, and they have a short duration (Becher, ; Yeager & Beihn, ).…”
Section: Discussionmentioning
confidence: 99%
“…The fast and reliable erectile response has been recently demonstrated in phase III trials, in which it has been shown that the majority of patients (n = 434) receiving alprostadil topical cream 300 μg had a time interval (from administration) to successful penetration attempts of 5-30 min. In addition, approximately 98% of the administered dose of Vitaros/Virirec is retained in the fossa navicularis of the penis, thus minimizing systemic diffusion of the drug [Becher, 2004;Yeager and Beihn, 2005].…”
Section: Biology and Mechanismmentioning
confidence: 99%